The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/hbm.25815
|View full text |Cite
|
Sign up to set email alerts
|

Using child‐friendly movie stimuli to study the development of face, place, and object regions from age 3 to 12 years

Abstract: Scanning young children while they watch short, engaging, commercially-produced movies has emerged as a promising approach for increasing data retention and quality. Movie stimuli also evoke a richer variety of cognitive processes than traditional experiments, allowing the study of multiple aspects of brain development simultaneously. However, because these stimuli are uncontrolled, it is unclear how effectively distinct profiles of brain activity can be distinguished from the resulting data.Here we develop an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…However, connectivity from movie-watching may be more predictive of function in some brain regions including visual cortex 32 , 41 , and our results are consistent with this conclusion. Movie-watching may also offer other advantages such as improved reliability of connectivity estimates 39 , 42 , reproducibility of brain activity across participants and data acquisition sites 43 , and suitability for studying developmental populations 44 , 45 . Nevertheless, the gradients could still be accurately reconstructed from connectivity at rest, and there may be scenarios where resting-state data would be advantageous, for instance if studying visually impaired populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, connectivity from movie-watching may be more predictive of function in some brain regions including visual cortex 32 , 41 , and our results are consistent with this conclusion. Movie-watching may also offer other advantages such as improved reliability of connectivity estimates 39 , 42 , reproducibility of brain activity across participants and data acquisition sites 43 , and suitability for studying developmental populations 44 , 45 . Nevertheless, the gradients could still be accurately reconstructed from connectivity at rest, and there may be scenarios where resting-state data would be advantageous, for instance if studying visually impaired populations.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to clarify the relationship between the language and the ToM networks, we examine responses in the frontal and temporal language areas to the standard verbal ToM contrast (false belief stories > false photograph stories; Saxe & Kanwisher, 2003; the same contrast as was used in Deen et al, 2015), but also to a non-verbal ToM contrast (mental events > physical interactions in a rich naturalistic stimulus-a fewminute-long Pixar film; Jacoby et al, 2016). Jacoby et al (2016) have previously shown that this nonverbal ToM contrast elicits a strong response in brain areas defined by the verbal ToM localizer (see also Richardson et al, 2018;Kamps et al, 2022).…”
Section: Introductionmentioning
confidence: 99%